5-Aminolevulinic Acid-Mediated Photodynamic Therapy on Hep-2 and MCF-7c3 Cells - Alvarez, María Gabriela (2007)
The cytotoxic effect of 5-aminolevulinic acid (ALA) induced protoporphyrin IX (PPIX) on two human carcinoma cell lines, MCF-7c3 cells and Hep 2 cells, was studied. In both cell lines, PPIX content depends on the ALA concentration and incubation time. The maximal PPIX content was higher in the MCF-7c3 cells, reaching a value of 8 μg/106 cells, compared to the Hep-2 cells, which accumulated 3.2 μg/106 cells. Treatment of cells with the iron chelator desferrioxamine prior to ALA exposure enhances the amount of PPIX, consequently diminishing enzymatic activity of ferroquelatase. Photo sensitization of the cells was in correlation with the PPIX content; therefore, conditions leading to 80% cell death in the MCF-7c3 cells provoke a 50% cell death in the Hep 2 cells. Using fluorescence microscopy, cell morphology was analyzed after incubation with 1 mM ALA during 5 hr and irradiation with 54 Jcm−2; 24 hr post-PDT, MCF-7c3 cells revealed the typical morphological changes of necrosis. Under the same conditions, Hep-2 cells produced chromatine fragmentation characteristic of apoptosis. PPIX accumulation was observed to occur in a perinuclear region in the MCF-7c3 cells; while in Hep-2 cells, it was localized in lysosomes. Different mechanisms of cell death were observed in both cell lines, depending on the different intracellular localization of PPIX.